Ruah está soprando as flores: mulheres e suas militâncias no fazer teológico feminista no Brasil - Melo, Flávia Valéria Cassimiro Braga (2021)
This research conducts an ethnographic study with six groups of Christian feminists articulated around a closed Facebook group called in this study Flores Insubmissas: Evangélicas pela Igualdade de Gênero, Frente Evangélica pela Legalização do Aborto, Católicas pelo Direito de Decidir, Vozes Marias, Rede de Mulheres Negras Evangélicas, and Projeto Redomas. These are women who fight against the traditional Christian engagements, permeated by the logic of patriarchy. The study was carried out through Cyber-Etnography and multisite ethnography, adopting participant observation, field diary records, and thirteen interviews. In this context, it was possible to accompany them in different trenches and militancy, in which the feminist theological practice, intertwined with its thematic approaches, placed them in different fronts and trenches. In my ethnographic journey I sought to understand how these women, by diluting the apparently inconconcilable barriers between feminism and Christianity to made them tools of struggle and militancy, becoming political subjects. Through this study I observed that among their main targets are, for example, the decriminalization of abortion, the confrontation against violence, the denunciation against racism, the inter-religious dialogue, the autonomy of women over their bodies, and the dissidents of gender and sexuality. Outside the borders, they are marginalized in different aspects, yet they are producing ruptures and managing to widen their tents, as well as counter patriarchal narratives and dialogue beyond the walls.